2015
DOI: 10.1016/j.ramd.2014.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean diet in a group of midlife women: the FLAMENCO project

Abstract: Objetivo. Evaluar los cambios en la composición corporal entre hombres y mujeres con sobrepeso y obesidad, 3 años después de finalizar la intervención de pérdida de peso de 6 meses.Método. Noventa y ocho sujetos (49 hombres) del proyecto PRONAF participaron voluntariamente en el estudio 3 años después de la intervención del mismo. Durante los 6 meses de intervención, todos siguieron una restricción calórica del 25-30% del gasto energético total diario, y siguieron un programa de entrenamiento o recomendaciones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Participants often reported that certain MIND diet foods were not typical of their culture and serving certain foods to family and friends were not acceptable, such as wholegrain pasta and bread. This finding is in support of previous research that found low consumption of wholegrains in a Spanish sample [ 84 , 85 ]. Baruth et al [ 86 ], found family to be a barrier to healthy eating.…”
Section: Discussionsupporting
confidence: 93%
“…Participants often reported that certain MIND diet foods were not typical of their culture and serving certain foods to family and friends were not acceptable, such as wholegrain pasta and bread. This finding is in support of previous research that found low consumption of wholegrains in a Spanish sample [ 84 , 85 ]. Baruth et al [ 86 ], found family to be a barrier to healthy eating.…”
Section: Discussionsupporting
confidence: 93%
“…Participants often reported that certain MIND diet foods were not typical of their culture and serving certain foods to family and friends were not acceptable, such as wholegrain pasta and bread. This finding is in support of previous research that found low consumption of wholegrains in a Spanish sample [85][86]. Baruth et al [87], found family to be a barrier to healthy eating.…”
Section: Discussionsupporting
confidence: 91%